Flexible nanogap polymer light-emitting diodes fabricated via adhesion lithography (a-Lith). (17th September 2018) - Wyatt-Moon, Gwenhivir; Georgiadou, Dimitra G; Zoladek-Lemanczyk, Alina; Castro, Fernando A; Anthopoulos, Thomas D
Abstract: We report the development of coplanar green colour organic light-emitting diodes (OLEDs) based on asymmetric nanogap electrodes fabricated on different substrates including glass and plastic. Using adhesion lithography (a-Lith) we pattern Al and Au layers acting as the cathode and anode electrodes, respectively, separated by an inter-electrode distance of <15 nm with an aspect ratio of up to 10 6 . Spin-coating the organic light-emitting polymer poly(9, 9-dioctylfluorene- alt -bithiophene) (F8T2) on top of the asymmetric Al–Au nanogap electrodes results in green light-emitting nanogap OLEDs with promising operating characteristics. We show that the scaling of the OLED's width from 4 to 200 mm can substantially improve the light output of the device without any adverse effects on the manufacturing yield. Furthermore, it is found that the light-emitting properties in the nanogap area differ from the bulk organic film, an effect attributed to confinement of the conjugated polymer chains in the nanogap channel. These results render a-Lith particularly attractive for low cost facile fabrication of nanoscale light-emitting sources and arrays on different substrates of arbitrary size.